Admixture in Mammals and How to Understand Its Functional Implications: On the Abundance of Gene Flow in Mammalian Species, Its Impact on the Genome, and Roads into a Functional Understanding. (30th October 2019) - Fontsere, Claudia; de Manuel, Marc; Marques‐Bonet, Tomas; Kuhlwilm, Martin
Abstract: Admixture, the genetic exchange between differentiated populations appears to be common in the history of species, but has not yet been comparatively studied across mammals. This limits the understanding of its mechanisms and potential role in mammalian evolution. The authors want to summarize the current knowledge on admixture in non‐human primates, and suggest that it is important to establish a comparative framework for this phenomenon in humans. Genetic observations in domesticated mammals and their wild counterparts are discussed, and a brief global overview on other clades is presented. Based on this, some of the consequences of gene flow, including incompatibilities and their genomic footprint, as well as adaptive introgression are discussed, and suggestions for a functional genomics approach are made. It is proposed that the field is moving beyond descriptive observations in single species, to a comprehensive analysis of admixture and its impact. Admixture is becoming an integral part of mammalian evolution. Abstract : Admixture appears to be common in evolution, suggesting that it should be studied comparatively across mammals. Here, gene flow in non‐human primates and domesticated and other mammals is discussed. Consequences of admixture are adaptive introgression and genetic incompatibilities with their genomic footprints, which need to be understood using functional genomics approaches.